Performance investigation of a battery thermal management system with microencapsulated phase change material suspension. (5th November 2020) - Li, Hua; Xiao, Xiangyu; Wang, Yanan; Lian, Chen; Li, Qingfeng; Wang, Zhengkun
Highlights: The microencapsulated phase change material suspension (MEPCMS) is applied in the BTMS. The battery temperature and pressure drop are used as the performance indexes. The effects of the adjustable parameters of the MEPCMS on the BTMS performance are analyzed. Improved design and results are obtained according to the analysis. Abstract: In electric vehicles, the performance of the battery thermal management system (BTMS) is closely related to the life and safety of the power batteries. Microencapsulated phase change material suspension (MEPCMS) has good thermal management property, and has been used in many fields of industry. In order to investigate the feasibility of applying MEPCMS to the BTMS, a BTMS model using liquid cold plates is established. It is found that compared with natural heat dissipation condition, using water or MEPCMS as the coolant can significantly reduce the maximum temperatures of the tabs and on the battery body at the end of 5C discharge, but increase the maximum temperature difference on the battery body. The effects of the flow rate of the MEPCMS, the volume fraction of the microencapsulated phase change material (MEPCM), the latent heat and the melting temperature range of the phase change material (PCM) on the thermal management performance are investigated. All these above design parameters can significantly affect the temperature distribution of the battery. Based on the analysis results, an improved design using MEPCMS as the coolant is obtained, and its performance is better than that using water.